Doping methods and properties of the solid solutions on AIᴵᴵBⱽᴵ crystals base - Atroshchenko, L.V.; Gal'chinetskii, L.P.; Galkin, S.N.; Katrunov, K.A.; Lalayants, A.I.; Lisetskaya, E.K.; Rybalka, I.A.; Ryzhikov, V.D.; Silin, V.I.; Starzhinskii, N.G.; Voronkin, E.F. (Functional Materials, 2005)
It has been shown that the composition and concentration of complex and radiative recombination centers in solid solution crystals in AIᴵᴵBⱽᴵ systems depends along what section of the concentration triangle is the solid solution obtained. Effects have been studied of the isovalent dopant and thermal treatment in different media upon optico-luminescent, structural and physico-chemical characteristics of solid solution of crystals in the nSe-nTe system. Встановлено, що склад і концентрація комплексних центрів випромінювальної комбінації кристалів твердих розчинів (ТР) у системах AIᴵᴵBⱽᴵ залежать від того, вздовж якого розрізу концентраційного трикутника відбувається утворення ТР. Досліджено вплив ізовалентної домішки і також термообробки у різних середовищах на оптико-люмінесцентні, структурні й фізико-хімічні характеристики кристалів ТР у системі nSe-nTe. Установлено, что состав и концентрация комплексных центров излучательной рекомбинации кристаллов твердых растворов (ТР) в системах AIᴵᴵBⱽᴵ зависят от того, по какому разрезу концентрационного треугольника происходит образование ТР. Исследовано влияние изовалентной примеси и термообработки в различных средах на оптико-люминесцентные, структурные и физико-химические характеристики кристаллов ТР в системе nSe-nTe.